Reader Reaction and Workplace Habits in the English Translation of French Proper Names in Canada - Mossop, Brian (Meta, 2007)
AbstractThis article looks at factors that might be involved in the translation of French place names and institution names into English in Canada: the anticipated reactions of readers; rules enunciated by clients, employers and style guides; the effects of workplace procedures (reduced quality control time; use of cut-and-paste translation). The possible translations of five proper names are discussed: Québec, Radio-Canada, Acadie, Commis-sion québécoise des libérations conditionnelles, Canada/canadien.